Perilla essential oil Pickering emulsion with sustained-release antibacterial properties and application thereof
By using composite particles prepared by chitosan and modified titanium dioxide, combined with Pickering emulsion technology, the stability of perilla essential oil in the food industry was solved, and its sustained release and antibacterial effects in food were achieved.
Patent Information
- Application Number
- CN202410929396.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-07-11
AI Technical Summary
The instability, light sensitivity, oxidation, water insolubleness and high volatility of perilla essential oil limit its application in the food industry.
CS-TiO2 composite particles were prepared by chitosan (CS) and modified titanium dioxide (TiO2). Perilla essential oil was combined with these composite particles by Pickering emulsion technology to form a stable Pickering emulsion.
This method not only improves the stability of perilla essential oil, but also gives it sustained release and antibacterial properties, realizing the dual functions of food preservation and biologically active delivery.
Smart Images

Figure CN118872694B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biotechnology, and in particular to a perilla essential oil Pickering emulsion with slow-release antibacterial properties and application thereof. Background Art
[0002] Essential oils (EOs) are widely recognized as ideal natural preservatives due to their Generally Recognized As Safe (GRAS) status and antibacterial and antioxidant properties. Perilla essential oil (PLEO) has attracted increasing attention not only for its aroma and potential as a natural preservative, but also for its health-promoting bioactivities such as antibacterial, insecticidal, antioxidant, anti-inflammatory, anticancer, antiallergic, and antidepressant effects. PLEO is a complex mixture of volatile molecules and other substances (including phenolic antioxidants) extracted from Perilla frutescens (L.) Britt, a medicinal and edible herb. Studies have found that PLEO can inhibit the growth of Staphylococcus aureus and other foodborne pathogens and suppress the production of exotoxins, which is mainly attributed to its bioactive components such as perillaldehyde, perillone, and limonene. However, the instability, photosensitivity, susceptibility to oxidation, water insolubility, and high volatility of PO greatly restrict its application, resulting in significant constraints on its practical application.
[0003] In the food industry, emulsions are one of the most effective delivery systems for delivering essential oils because the interfacial coating / film layer can protect the essential oils and their components and minimize the volatilization of aromatic and bioactive volatile compounds. Traditional emulsions stabilized by surfactants or amphiphilic polymers tend to become unstable over time due to the high surface energy at the interface between the two immiscible phases (which are prone to coagulation, flocculation, and Ostwald ripening during storage). Therefore, Pickering emulsions were developed, which use insoluble colloidal particles as almost irreversible adsorbed interfacial particle stabilizers to prevent droplet coagulation to deliver essential oils, thereby improving the stability of the emulsion. The present invention intends to develop a Pickering emulsion of perilla essential oil to expand the application field of perilla essential oil. Summary of the invention
[0004] The purpose of the present invention is to provide a perilla essential oil Pickering emulsion and a preparation method and application thereof to solve the problems existing in the above-mentioned prior art. The perilla essential oil Pickering emulsion has antibacterial activity while slowly releasing perilla essential oil, so the emulsion has the dual functions of food preservation and biological activity delivery.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] The present invention provides a method for preparing a perilla essential oil Pickering emulsion, comprising the following steps:
[0007] The sodium laurate and titanium dioxide particles are mixed and reacted to obtain modified titanium dioxide particles;
[0008] adding the modified titanium dioxide particles into a chitosan solution to react and obtain chitosan-titanium dioxide composite particles;
[0009] dispersing the chitosan-titanium dioxide composite particles in water to obtain a chitosan-titanium dioxide composite particle suspension;
[0010] The perilla essential oil is added dropwise to the chitosan-titanium dioxide composite particle suspension, and the perilla essential oil Pickering emulsion is obtained after homogenization.
[0011] Furthermore, the mass ratio of the sodium laurate to the titanium dioxide particles is 0.75:5.
[0012] Furthermore, the pH value of the mixed reaction is 5.0.
[0013] Furthermore, the temperature of the mixed reaction is 40° C. and the time is 4 hours.
[0014] Furthermore, the mass ratio of chitosan in the chitosan solution to the modified titanium dioxide particles is 1:(0.1-1).
[0015] Furthermore, the mass ratio of the chitosan to the modified titanium dioxide particles is 1:(0.5-1).
[0016] Furthermore, the mass ratio of the chitosan to the modified titanium dioxide particles is 1:0.5.
[0017] Furthermore, the volume ratio of the perilla essential oil to the chitosan-titanium dioxide composite particle suspension is 1:1.
[0018] The present invention also provides a perilla essential oil Pickering emulsion prepared according to the above preparation method.
[0019] The present invention also provides application of the perilla essential oil Pickering emulsion in preparing an antibacterial agent or a preservative.
[0020] The present invention discloses the following technical effects:
[0021] The present invention uses chitosan (CS) and titanium dioxide (TiO2) to prepare CS-TiO2 composite particles. Under the condition of pH 5.0, after modifying titanium dioxide with sodium laurate, 0.1%-3% titanium dioxide is successfully introduced into the CS matrix. The CS-TiO2 composite particles prepared by the present invention form a stable and flexible three-dimensional gel network film on the oil / water interface, mainly showing elastic solid-like properties and high anti-interference ability, among which the CS-TiO2-0.5% composite material shows unique advantages. The PLEO Pickering emulsion stabilized by these composite particles is a non-Newtonian pseudoplastic fluid with shear thinning, slow release and antibacterial properties, among which the emulsion stabilized by CS-TiO2-0.5% and CS-TiO2-1% composite materials has the highest antibacterial effect on Escherichia coli and Staphylococcus aureus. Studies have found that Fickian diffusion and sustained slow release of PLEO occur in all Pickering emulsions, and the Rigter-Peppas model is the best model to describe the release of PLEO from the emulsion. The sustained release behavior was positively correlated with the interfacial pressure, composite particle size, composite particle potential, composite contact angle, emulsion particle size, and emulsion potential, but negatively correlated with the diffusion rate, permeation rate, release kinetics, and release rate. The CS-TiO2-stabilized PLEO emulsion delivered the health-promoting properties of CS and PLEO and had an antibacterial effect while sustained-releasing PLEO. Therefore, this emulsion had the dual functions of food preservation and bioactive delivery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 FTIR spectra of composite particles containing a fixed concentration (1%, W / W) of chitosan (CS) and different concentrations (0%-3%, W / W) of TiO2;
[0024] Figure 2 It is a statistical diagram of the particle size of composite particles containing a fixed concentration (1%, W / W) of CS and different concentrations (0%-3%, W / W) of TiO2;
[0025] Figure 3 The volume distribution diagram of composite particles containing a fixed concentration (1%, W / W) of CS and different concentrations (0%-3%, W / W) of TiO2;
[0026] Figure 4ζ potential statistics of composite particles containing a fixed concentration (1%, W / W) of CS and different concentrations (0%-3%, W / W) of TiO2;
[0027] Figure 5 Atomic force microscopy images of composite particles containing a fixed concentration (1%, W / W) of CS and different concentrations (0%-3%, W / W) of TiO2;
[0028] Figure 6 The scanning electron micrographs of composite particles containing a fixed concentration (1%, W / W) of CS and different concentrations (0%-3%, W / W) of TiO2;
[0029] Figure 7 The three-phase contact angle diagram of composite particles containing fixed concentration (1%, W / W) CS and different concentrations (0%-3%, W / W) of TiO2;
[0030] Figure 8 The interfacial tension (A), interfacial pressure (B), the relationship between the square root of time (t1 / 2) and the interfacial pressure (C), and the time function ln[(π 10800 -π t ) / (π 10800 -π0)] (D), interface pressure function interface viscoelastic modulus (E), interface elastic modulus (F), interface viscosity modulus (G) and time-varying (H) Statistical graph;
[0031] Fig. 9 The frequency scanning and amplitude scanning results are shown in Figure 1. Among them, A and B are the interface viscoelastic modulus (A) and (B) as a function of frequency; C and D are the interfacial viscoelastic modulus (C) and (D) as a function of amplitude time;
[0032] Fig.10 The Lissajous diagram of the stable oil-water interface of CS (1%, W / W) and TiO2 (0-3%, W / W) composite particles was obtained by amplitude scanning (ΔA / A=5%-30%);
[0033] Fig.11 The results of measuring the s factor during tension (A) and compression (B) by amplitude scanning (ΔA / A = 5% to 30%) at the oil-water interface stabilized by chitosan (CS)-TiO2 composite particles of different concentrations;
[0034] Fig.12Droplet size (A), zeta potential (B) and confocal laser microscopy images (C) of CS (1%, W / W) and TiO2 (0%-3%, W / W) composite particle-stabilized emulsions;
[0035] Fig.13 The results of the rheological behavior test of the emulsion of CS (1%, W / W) and TiO2 (0%-3%, W / W) composite particles; wherein A and B are the functions of the storage modulus G′ (A) and the loss modulus G″ (B) and the frequency; C is the function of the storage modulus G′ and the stress; D is the function of the emulsion viscosity and the shear rate (D);
[0036] Fig.14 The sustained release curve (A) and sustained release percentage (B) of EO in emulsions stabilized by composite particles of CS (1%, W / W)-TiO2 (0% to 3%, W / W) at different concentrations, and the antibacterial effect diagram on Escherichia coli and Staphylococcus aureus (C);
[0037] Fig.15 The results of the correlation analysis between the interfacial adsorption and stability of the emulsion and the sustained release of the composite particles and the emulsion (A) and the correlation diagram (B). DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] Example 1
[0044] 1. Materials and Methods
[0045] 1.1 Materials and Chemicals
[0046] TiO2 (purity: 99.3wt%; particle size: 5-10nm) powder was from Beijing Huawei Ruike Chemical Co., Ltd.; PLEO was from Sitaibo Technology Co., Ltd. (Tianjin, China); CS was purchased from (molecular weight: 150kDa; deacetylation degree: 95%; viscosity: 100-200mPa.s; CAS: 9012-76-4); n-hexane and isopropanol were purchased from Wuhan Aolite Biotechnology Co., Ltd.; sodium laurate, Nile red and blue fluorescent dye were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; blank drug sensitivity test kit was purchased from Tianjin Sitaibo Technology Co., Ltd.; blank drug sensitivity paper was purchased from Guangzhou Kanglong Biotechnology Co., Ltd.; potassium bromide was purchased from Shanghai Keats Biochemical Technology Co., Ltd.; fluorescent dye was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; other reagents were of analytical grade.
[0047] 1.2 Preparation of composite particles and emulsion
[0048] Modification of titanium dioxide particles: Sodium laurate (0.75 g) was dissolved in 70 mL of deionized water (pH 5.0), and then titanium dioxide particles (5.0 g) were added. The mixture was magnetically stirred at 40°C for 4 h, vacuum filtered, washed with deionized water, and dried at 50°C for 3 h to obtain modified TiO2 particles.
[0049] Preparation of CS-TiO2 composite particles: CS was added to deionized water acidified with acetic acid (pH 5.5) at room temperature, and the mixture was stirred continuously using a magnetic stirrer (DF-101Z, China) until it was completely dissolved and the mass concentration reached 1%. Then, the modified TiO2 particles were added to the CS solution at a ratio of 0, 0.1%, 0.3%, 0.5%, 1% or 3% (weight ratio). The CS solution was homogenized using a homogenizer (IKAT25digital Germany) at a speed of 15000 r / min and an ice-water bath for 3 min to ensure that the mixture was completely dissolved and then formed into CS-TiO2 composite particles. A portion of the CS-TiO2 composite particles was freeze-dried using a freeze dryer (LGJ-12, vacuum freeze dryer, China).
[0050] Preparation of Pickering emulsion: 0, 0.1%, 0.3%, 0.5%, 1% or 3% (weight ratio) of CS-TiO2 composite particles were dispersed in 5 mL of deionized water to obtain a CS-TiO2 composite particle suspension. Then, PLEO was added dropwise to the CS-TiO2 composite particle suspension until the ratio reached 1:1 (v / v). Then, the homogenizer was used at a speed of 16000 r / min and an ice-water bath for 3 min.
[0051] 1.3 Characteristics of CS-TiO2 composite particles
[0052] 1.3.1 Fourier transform infrared spectroscopy (FTIR) analysis
[0053] ATR-FTIR spectrometer (Nicoleti S50, Thermo, Waltham, USA) was used at 400 cm -1 Up to 4000cm -1 Fourier transform infrared spectra of commercial CS, commercial TiO2, modified TiO2 nanoparticles, and CS-TiO2 composites were collected in the wavelength range with a resolution of 4 cm -1 , scanned 32 times. Each dried sample was mixed with potassium bromide (KBr; spectral grade) at a ratio of 95:5 (weight ratio), and the mixture was then ground and pressed into thin sheets for spectral analysis. Pure KBr was used for background correction.
[0054] 1.3.2 Particle size and zeta potential of CS-TiO2 composite particles and derived PLEO emulsions
[0055] The particle size and potential of the CS-TiO2 composite particles and their stably derived PLEO emulsions were measured separately. Before measuring the particle size and zeta potential using a particle size analyzer (Mastersizer 3000, Malvern, UK), the CS-TiO2 composite particles were dispersed in deionized water at a concentration of 0.1 mg / mL, and the PLEO emulsion samples were diluted 100 times with ultrapure water and then analyzed using a particle size analyzer (Mastersizer 3000, Malvern, UK).
[0056] 1.3.3 Microscopic examination of CS-TiO2 composite particles
[0057] Scanning electron microscopy (SEM): The freeze-dried CS-TiO2 composite particles were gold-coated for 180 seconds using a sputter coater (Quorum Technologies, West Sussex, UK) and then examined using a scanning electron microscope (S-4800, Hitachi, JPN) at 5.00 kV.
[0058] Atomic force microscopy (AFM): The surface morphology of the composite particles was examined using an atomic force microscope (MultiMode8-HR, Bruker). CS-TiO2 composite particles were deposited on freshly exfoliated mica at a 10-fold dilution and dried for 12 h before obtaining AFM amplitude images with a scan size of 2 μm × 2 μm.
[0059] 1.3.4 Contact angle of CS-TiO2 composite particles
[0060] The contact angle of the CS-TiO2 composite particles was measured using a video optical contact angle meter (OCA-25, Dataphysicals Instruments GmbH, Germany). The freeze-dried CS-TiO2 powder was pressed into smooth discs using a tablet press (HY-30) and placed in a transparent cuvette containing PLEO. A motor-driven automatic ejector sprayed 5 μL of water onto the surface, and the droplet image was taken after balancing at room temperature (23 ± 1 ° C) for 30 seconds.
[0061] 1.4Interfacial behavior of CS-TiO2 composite particles
[0062] 1.4.1 Dynamic interfacial tension and adsorption kinetics
[0063] Before measuring with an optical contact angle meter (OCA-25, Data PhysiCS Instruments GmbH, Germany) at room temperature (23 ± 1 ° C), a 10 μL sample droplet was placed in an optical glass cuvette filled with PLEO and allowed to stand for 1.5 h. The behavior of the droplet was recorded by video, and the interfacial tension (γ) was calculated using the following formula.
[0064]
[0065] Where P1-P2 is the interface pressure difference, γ is the interface tension, and R1 and R2 are the radii of curvature. The interface pressure (π) is calculated using the following formula:
[0066] π=γ0-γ
[0067] Here, γ0 is the interfacial tension of water.
[0068] The adsorption process includes diffusion, permeation and rearrangement (such as recombination). In the initial adsorption stage, the surface pressure (π) related to the adsorption time (t) was estimated according to the following formula.
[0069] π=2C0KT(Dt / 3.14) 1 / 2
[0070] Where C0 is the concentration of the continuous phase, K is the Boltzmann constant, T is the absolute temperature, D is the diffusion coefficient, and t is the adsorption time.
[0071] If the adsorption process is controlled by diffusion, π is 1 / 2 The curve will show a linear relationship, and the slope represents the diffusion rate of the composite particles (K diff ). The analysis of permeability and rearrangement rate adopts the following formula proposed by Graham and Philips:
[0072]
[0073] Among them, π f ,π0 and π t are the surface pressure at the end of adsorption, the beginning of adsorption and each corresponding time point (t), respectively, k i is the first-order rate constant.
[0074] The viscoelastic modulus was measured at room temperature (23±1°C), an oscillation frequency of 0.1 Hz, and an oscillation amplitude of 10% using the following formula:
[0075]
[0076] A=A0sin(ωt)
[0077] E=dσ / (dA / A)=-dπ / dlnA
[0078]
[0079]
[0080] Where: is the phase angle; σ, σ0 and A, A0 are the expansion stress and surface area at time t and time zero; ω is the angular frequency; E d 、E v and E are the elastic modulus, viscous modulus and viscoelastic modulus.
[0081] 1.4.2 Amplitude and frequency sweep measurements
[0082] Amplitude scanning: At room temperature (23±1°C) and a frequency of 0.1 Hz, an amplitude scan was performed on the droplet in adsorption equilibrium to measure the droplet deformation (ΔA / A) in the range of 5%-30%.
[0083] Frequency sweep: After 1.5 h of equilibration, frequency sweeps in the range of 0.02-0.1 Hz were measured at room temperature (23±1°C) and 10% strain (within the linear viscoelastic region).
[0084] 1.4.3 Lissajous curve
[0085] The relationship between droplet deformation and interface structure was examined by Lissajous plots. Lissajous plots use interface pressure and droplet deformation as independent and dependent variables, respectively, and use amplitude sweeps to study nonlinear interfacial rheological behavior. The shear strain-stiffness ratio (S factor) was calculated using the following formula: S<0 indicates strain softening, S>0 indicates strain hardening, and S=0 indicates elastic response.
[0086] S e =(E L,E -E M,E ) / E L,E
[0087] S c =(E L,C -E M,C ) / E L,C
[0088] Among them, E L,E and E M,E E is the maximum strain modulus and minimum strain modulus during tension. L,C and E M,C are the maximum strain modulus and minimum strain modulus in compression, respectively.
[0089] 1.5 Characteristics of essential oil emulsion stabilized by CS-TiO2 composite particles
[0090] 1.5.1 Confocal laser scanning microscopy (CLSM) measurement
[0091] CLSM was used to observe the microstructure of the emulsion. First, Nile blue (2%, w / v) and Nile red (0.5%, w / v) were dissolved in isopropanol, respectively, and then mixed together in a ratio of 1:1 (v / v). An equal amount (40 μL) of the mixed dye was added to 1 mL of the emulsion for 30 min and allowed to color in the dark. Subsequently, 5 μL of the colored sample was detected on the operating table using a laser confocal scanning microscope (LSM7810DUO, Zeiss, Germany). The excitation wavelengths were set to 488 and 633 nm.
[0092] 1.5.2 Rheological properties
[0093] The rheological properties of the emulsions were evaluated using a rheometer (HAAKE GmbH, Germany). Rheological measurements were performed at room temperature (23 ± 1 °C) using 40 mm parallel plates (gap = 1.0 mm). The relationship between shear rate (D, s-1) and apparent viscosity (η, Pa.s) was analyzed using the following formula:
[0094] lnη=lnk+(n-1)lnD
[0095] Wherein, k is the consistency coefficient (Pasn) and n is the flow characteristic index.
[0096] 1.6 Release characteristics and kinetics of PLEO in emulsion
[0097] Place PLEO and CS-TiO2 composite particle stabilized PLEO emulsion (5 mL each) into a beaker, and accurately measure and record the weight. The relative cumulative evaporation rate is calculated as follows:
[0098] CR=1-M t / M0
[0099] Where CR is the cumulative evaporation rate, M t is the oil content of the emulsion at time t (%), and M0 is the initial oil content of the emulsion (%).
[0100] Various kinetic models (zero-order release, Higuchi, Rigter-Peppas, and Korsmeyer-Peppas kinetic models) were employed to evaluate the release mechanism of PLEO from the emulsions, which are summarized below.
[0101] S t =K0t+C0
[0102]
[0103] S t =K2t n
[0104] ln t =nlnt+ln K
[0105] Among them, S t represents the cumulative evaporation percentage, t represents time (d), C0 is a constant, K0, K1 and K2 are the zero-order, Higuchi and Riegert-Peppers constants, respectively, and n is the release mechanism parameter.
[0106] 1.7 Antibacterial effect achieved by sustained release of antibacterial agent from emulsion stabilized by CS-TiO2 composite particles
[0107] The antibacterial effect of composite particle-stabilized EO emulsions against two different bacteria (Escherichia coli and Staphylococcus aureus) was evaluated according to published procedures. Briefly, a 5 μL × 10 6 CFU / mL) was inoculated into agar medium. An equal amount (15 μL) of PLEO or a composite particle-stabilized EO emulsion containing an equal amount of EO was smeared on a sensitive circular paper disc. These paper discs were then incubated upside down in a 37°C incubator for 7 days, and the changes in the inhibition zone were detected.
[0108] 1.8 Statistical analysis
[0109] All experiments were performed in triplicate and the data were reported as “mean ± standard deviation.” One-way analysis of variance (ANOVA) was performed using statistical analysis software (SPSS26, Chicago, IL, USA) to determine the significant differences between the mean values (P < 0.05).
[0110] 2. Results and Discussion
[0111] 2.1 Characteristics of composite particles
[0112] Figure 1 The FT-IR spectra of CS-TiO2 composite particles are shown, as well as the spectra of the starting materials, commercial CS, commercial TiO2, and modified TiO2 used to make such composite particles. The FT-IR spectrum of CS contains the wavelength of 3400 cm -1 (derived from NH and OH stretching vibrations), 2900cm- 1 (derived from aliphatic CH stretch), 1636cm -1 (The characteristic peak of CS is derived from the in-plane NH bending vibration of the NH2 group in the glucosamine unit) and the typical signal near 1538 cm - 1 (derived from the stretching vibration of C=O), 1405 cm -1 (derived from the CO stretching vibration of the primary alcohol group), 1378 cm -1 (derived from CN stretching associated with amide III), 1152 cm -1 (derived from the asymmetric expansion and contraction of the COC bridge) and 1020-1063cm -1 (derived from COC and CO stretching). The spectrum of TiO2 modified with sodium laurate is at 3458 cm -1 and 1636cm -1 There is a signal band at 2850cm (derived from the stretching and bending vibration of hydroxyl OH related to water). -1 Nearby (derived from the CH stretching vibration of sodium laurate), at 1700cm -1Nearby (strong carbonyl absorption band of sodium laurate), 1400-1550cm -1 (derived from CH2 and CH3 bending vibrations of sodium laurate), 1400-1300cm -1 Range (derived from Ti-O-Ti bonds and Ti-OH bonds in TiO2), 500-1000cm -1 (The characteristic band of TiO2 is derived from the stretching vibration of Ti-O and Ti-O-Ti). The Fourier transform infrared spectra of commercial CS and modified TiO2 were compared with the spectrum of CS-TiO2 composite particles, and the interaction between commercial CS and modified TiO2 was found. Compared with the CS sample, the CS-TiO2 sample has a strong peak at 3458 cm -1 The peaks near 2850cm became broadened and shifted less, indicating that the -OH groups on CS were involved in the interaction between CS and TiO2. This broadening effect varied with the concentration of TiO2 in the CS-TiO2 composite. -1 and 1700cm -1 The intensities of the two strong signal peaks near the 2470 nm and 2450 nm increase with the increase of TiO2 concentration. This phenomenon related to sodium laurate and some signal bands from TiO2 in CS-TiO2 samples with high TiO2 content (such as 3458 cm -1 1400-1300cm -1 and 500-1000cm -1 ) indicates that too high TiO2 concentration may lead to incomplete recombination of modified TiO2 and CS, and the presence of "free" unreacted TiO2 in the form of TiOH in the solution. 1400-1300cm -1 and 500-1000cm -1 The change in the intensity of the nearby signals further indicates the ligand interaction between CS and TiO2 particles. -1 The high similarity in the signal range suggests that TiO2 was successfully immobilized in the CS matrix, which may be achieved through the interaction between the -OH and / or -NH2 groups of the CS chains and the acidic groups of TiO2NPs through hydrogen bonding or even covalent bonding. In addition, ion pairing between protonated CS and ionized sodium laurate may be formed through the amino and carboxyl groups.
[0113] The differences in particle size, volume distribution, and zeta potential between CS-TiO2 samples and CS or TiO2 samples further indicate the interaction between CS and TiO2 in the CS-TiO2 system ( Figure 2-4). d4,3 and d3,2 (volume-weighted mean diameter and area-weighted mean diameter, respectively) represent the particle size of the tested samples, which increases with the increase of TiO2 concentration in the range of 0-0.5%, but when the TiO2 concentration further increases in the range of 0.5-3%, the particle size decreases more slowly, with the peak value appearing at a TiO2 concentration of 0.5% (5.05 μm) ( Figure 2 ). Figure 3 The difference in particle size distribution between CS samples and CS-TiO2 samples, as well as the effect of TiO2 concentration on the average particle size distribution of CS-TiO2 samples are shown.
[0114] like Figure 4 As shown, the trend of positive charge changing with TiO2 concentration is the same as the trend of particle size changing with TiO2 concentration ( Figure 2 ), the highest zeta potential value appears when the TiO2 concentration is 0.5% (54.6mV). Studies have found that the zeta potential of TiO2 nanoparticles in water suspension is affected by factors such as pH value, ion concentration and charge. The pH value can monitor the following changes: TiOH2 + , TiOH, TiO - In aqueous media with a neutral pH, the zeta potential of TiO2 nanoparticles may be weakly positive because water molecules can occupy the vacancies between oxygen molecules, producing adsorbed -OH groups, thereby changing the electronic structure of the nanoparticles and making them positively charged. In a slightly acidic water environment, TiO2 can be converted into a protonated state TiOH2 + , so that the TiO2 particles have a higher positive zeta potential. When the TiO2 concentration is in the range of 0-0.5%, the increase in the amount of TiO2 fills the network space between CS molecules, which not only increases the size of the CS-TiO2 composite particles, but also increases the positive potential of the composite particles. When the TiO2 concentration is further increased (from 0.5% to 3%, especially from 1% to 3%), in addition to the positively charged TiOH2 that has interacted with the negatively charged carboxyl groups of the CS matrix, + In addition to TiO2 and TiOH, there will be too much TiO2 in an unbound state, that is, TiO2 with zero charge. This countercharge interaction can lead to a reduction in charge neutralization particle size, while the appearance of unbound TiO2 and the countercharge interaction will lead to an increase in surface hydrophobicity. In addition, some unbound TiO2 may react with CS and appear in the aqueous phase in the form of TiOH, thereby increasing the local pH and causing further deprotonation of TiOH to TiO - , a negatively charged domain is generated on the surface of the composite material to repel surface water molecules and interact with H +Therefore, the particle size and positive potential of CS-TiO2 composite particles with TiO2 content higher than 0.5% decreased. When the TiO2 concentration reached 3%, the TiO2 coverage on the CS surface increased, and the unbound zero-charged TiO2 and negatively charged TiO - As the number of ions increases, the positive potential decreases significantly.
[0115] Figure 5 and Figure 6 Showing the differences in surface morphology and microstructure caused by the addition of TiO2 to the CS matrix. Atomic force microscopy images ( Figure 5 ) showed that there were significant differences in the surface roughness and patterns of the samples tested, and the similarity of CS-TiO2 samples containing 0.3%-1% TiO2 was relatively high. The CS samples showed a haploid distribution, and the CS polymer was embedded in the matrix in a spherical structure. Dense, narrow extruded needle-like structures of varying numbers and heights appeared on the surface of the CS-TiO2 samples (except for the samples with a TiO2 content of 3%), indicating that the TiO2 particles have been successfully coated on the CS surface. The surface morphology of the CS-TiO2 sample containing 3% TiO2 is completely different, showing a uniform cumulative distribution of particles, indicating that there may be too many spherical TiO2 particles on the formed organic-inorganic composite material. Scanning electron microscope image ( Figure 6 ) showed that with the increase of TiO2 addition, the continuity and density in the matrix also increased, indicating that in the CS-TiO2 system, a continuous interface film was formed between TiO2 and CS, and the small spherical TiO2 particles were successfully integrated into the CS matrix. When the TiO2 concentration reached 1% or 3%, small spherical TiO2 particles were clearly seen on the CS-TiO2 composite.
[0116] Figure 7 The results show that the addition of modified TiO2 increases the contact angle value. The smaller the contact angle, the stronger the wetting ability and hydrophilicity. The contact angle of the CS sample is 90.1°. The contact angle value is maximum when the addition amount of modified titanium dioxide is in the range of 0.3-1%. When the titanium dioxide concentration reaches 3%, the contact angle decreases again, which may be due to the excess hydrophilic titanium dioxide and the formation of negatively charged areas on the surface of the composite material (as mentioned above).
[0117] 2.2 Oil-water interface behavior of CS-TiO2 composite particles
[0118] 2.2.1 Dynamic interfacial tension and interfacial expansion rheology
[0119] The colloidal behavior at O / W interfaces generally involves three processes: diffusion, permeation, and rearrangement / reorganization. Figure 8 Figure A shows that the interfacial tension of all samples decreases over time, which is due to the continuous adsorption of particles at the O / W interface. Figure 8 Figure A also shows that the interfacial tension of the CS sample is the highest during the investigation period. As the TiO2 concentration increases, the interfacial tension decreases (TiO2 concentration range is 0.1-0.5%) and then increases again (TiO2 concentration range is 0.5-3%), which is opposite to the change trend of the interfacial pressure ( Figure 8 (B). These results may be attributed to the enhanced multilayer adsorption of the interfacial layer by the added TiO2, as well as the relatively large particle size and zeta potential at TiO2 concentrations around 0.5%. More composite entities can be attached to the outer layer to fill the gaps created by the previous irreversible adsorption process, and this secondary adsorption process involving various intermolecular forces is considered as reversible adsorption due to its low desorption energy. With the addition of more and more TiO2 particles, the TiO2 loading may become oversaturated, making some composite particles unable to be adsorbed at the interface, due to the presence of excess TiO2 after the previous observation of interfacial behaviors of irreversible and reversible adsorption processes of protein particles at the O / W interface.
[0120] Figure 8 B and C describe the interface pressure (π) with time (t) or the square root of time (t 1 / 2 ). When the composite particles are adsorbed on the O / W interface by diffusion, the obtained π and t 1 / 2 The relationship between the two becomes linear, and the corresponding slope represents the diffusion rate constant (K diff Table 1 shows that, except for CS and CS-TiO2-0.1% (both are statistically the same), CS-TiO2-1% and CS-TiO2-3% (CS-TiO2-1%>CS-TiO2-3%), K diff The value generally increases with increasing concentration, which indicates that TiO2 concentration is the main factor affecting the diffusion rate of composite particles from the bulk phase to the interface. Compared with the CS-TiO2-1% sample, the diffusion rate constant of the CS-TiO2-3% sample is lower, which may be due to the presence of excess TiO2 particles, which causes changes in the molecular interactions of the composite particles and their interactions with the interface. When the TiO2 concentration is 3%, the zeta potential is the lowest, which affects the rapid diffusion of the composite particles to the interface. The composite particles that have been adsorbed on the interface layer will induce repulsion and steric hindrance effects on the surrounding unadsorbed composite particles, thereby affecting the further diffusion of the composite particles. Similar diffusion behavior was previously found when myofibrillar protein particles diffused to the O / W interface. For all test samples in the present invention, the initial adsorption process of the composite particles on the interface is a diffusion-controlled process. As the composite particles gradually establish an energy barrier in the interface layer, after a short period of diffusion-controlled adsorption, the adsorption rate slows down, and the adsorption process is restricted or even offset by the composite particles that have penetrated and precipitated on the interface.
[0121] Table 1 Kinetic parameters of adsorption of chitosan (CS)-TiO2 composite particles at the oil-water interface
[0122]
[0123] Note: Diffusion rate: K diff , penetration rate: K p , recombination rate: K r , interface pressure at the end of adsorption: π 5000 , adsorption start interface pressure: π0; K diff , K p , K r The values are expressed as "mean ± standard deviation". Different letters (ae) in the same column indicate significant differences (P < 0.05).
[0124] Figure 8 D shows ln[(π 10800 -π t ) / (π 10800 The relationship between -π0)] and t shows two linear regions. The initial slope represents the first-order permeability constant (K p ), and the subsequent slope corresponds to the first-order recombination rate constant (K r ). Table 1 shows that the permeability (K p ) increases with the increase of TiO2 concentration (0.1%-1%), which indicates that the positively charged TiOH2 + The counter-charge interaction between TiOH and the negatively charged carboxyl groups of the CS matrix leads to a gradual enhancement of the charge neutralization effect and a decrease in the size of the composite particles, which can overcome the interfacial energy barrier. When the TiO2 concentration reaches 3%, K p This may be due to the presence of too many unbound TiO2 particles, which interfere with the interaction of composite particles at the interface while increasing the hydrophilicity. As shown in Table 1, K r The changing trend of (recombination rate) and K diff and K p Different. r Value greater than K p This indicates that the permeation process is slower than the rearrangement process in each sample studied. In addition to the above influencing factors, K r The values may also be related to the contact angles of CS and CS-TiO2 samples. In summary, the adsorption process of composite particles on the interface is diffusion-controlled initially, then the adsorption rate slows down, and the following even phenomenon occurs: the adsorbed composite particles act as “new adsorbents” and “repulsive substances” for simultaneous adsorption and repulsion, and then the composite particles rearrange themselves around the interface.
[0125] As shown in the E-π diagram ( Figure 8As shown in Figure 5E), with the increase of π, the E of the CS sample and the CS-TiO2 sample increased slightly or greatly, respectively, which indicates that the CS-TiO2 particles were continuously adsorbed at the O / W interface to form a viscoelastic interface film. The slope values of the E-π graph were all greater than 1, indicating that the molecular interaction between the adsorbed particles was stronger. The slopes of the E-π graph were different (CS = 1.007; CS-TiO2 was in the range of 5.959-14.253), indicating that the intermolecular forces involved in the adsorption layer of the tested particles at the O / W interface were different in strength. Therefore, within the tested TiO2 concentration range, the CS-TiO2 composite particles all exhibited ideal adsorption behavior. In order to further study the formation of the viscoelastic film, the elastic modulus (E d ) and viscous modulus (E v ) The interfacial viscoelastic modulus (E) of the system was evaluated to explore the mechanical behavior of the emulsion at the interface (i.e., solid or liquid behavior). Figure 8 Figures F and G show that the behavior of CS-TiO2-3% (initially rising rapidly and then almost leveling off) is completely different from that of the other samples (initially rising slowly and then rising sharply). v The values show an upward trend. Figure 8 H shows the CS or CS-TiO2 composite particles The relationship between time. A value less than 1 indicates that the interface layer mainly exhibits elastic properties (which is beneficial to the stability of the emulsion). The smaller the value, the stronger the elasticity. When the TiO2 concentration increases, the interface layer formed by the CS-TiO2 composite particles becomes more elastic. The entire CS-TiO2-0.5%, CS-TiO2-1%, or CS-TiO2-3% The graphs are all below 1, indicating that the interfacial films formed by these composite particles have high stability. Compared with the CS-TiO2-0.1% sample and the CS sample, the interfacial film formed by CS-TiO2-0.3% takes a shorter time to transition from a viscous interfacial layer to an elastic interfacial layer. After a period of time, It turns into a negative value, which may reflect the reverse adsorption of particles on the interface and the reactivation of related adsorption processes, which leads to the destruction of the interfacial layer. In summary, CS-TiO2 composite particles can form a flexible solid film layer at the O / W interface.
[0126] 2.2.2 Frequency sweep and amplitude sweep
[0127] Fig. 9 It shows that the O / W interface of CS-TiO2 composite particles is stable at the frequency ( Fig. 9 A and B) and amplitude ( Fig. 9Elastic modulus under conditions C and D in Figure 2. Regardless of frequency scanning or amplitude scanning, all samples obtained The values are all less than 1, indicating that the interface layers formed by these composite particles at the O / W interface are mainly elastic, have solid-like properties and high anti-interference ability. Fig. 9 Figure A shows that the composite expansion modulus of the interfacial film increases with frequency, a behavior that can be explained by a relaxation mechanism. At low frequencies, the composite particles can rapidly reorganize and crosslink at the interface, allowing them to resist increases in interfacial tension (as indicated by a relatively low viscoelastic modulus). At high frequencies, the viscoelastic modulus increases for all samples examined, and CS-TiO2 composite particles with a higher TiO2 concentration exhibit a higher rate of diffusion from the bulk to the interface, making them more resistant to frequency perturbations (larger viscoelastic modulus). The relative strength of each sample increases with increasing frequency. The values are decreasing, which further confirms that they have a well-structured interface film with anti-interference ability. The change is related to the frequency. Fig. 9 C and D in the figure describe the functional relationship between the interface viscoelastic modulus and the amplitude. E and The trend of amplitude change is related to E and The trend of change with frequency is opposite. In the amplitude range of 5%-30%, The values are all lower than 1 ( Fig. 9 D), which confirms that the interfacial film formed by each particle studied is mainly elastic. The CS-TiO2-3% sample behaves very differently (e.g., its The value is closer to 1), which indicates that its interface layer structure may tend to be damaged because the excessive amount of unadsorbed TiO2 destroys the interface structure.
[0128] 2.2.3 Lissajous plot
[0129] Lissajous plots can more accurately represent the strain information during amplitude sweeps because they can study the nonlinear rheological behavior of complex interfaces during expansion oscillations. Fig.10Lissajous plots obtained during amplitude sweeps at the O / W interface (ΔA / A = 5%, 10%, 15%, 20%, 25% and 30%) are shown. The upper part of the Lissajous plot represents the extension of the interface, while the lower part represents compression. At smaller strain amplitudes, most of the elastic Lissajous plots exhibit different narrow closed shapes: linear (CS-TiO2-0.1%, CS-TiO2-0.3% and CS-TiO2-0.5%) or narrow elliptical (CS-TiO2-1%) (except for the CS-TiO2-3% sample, whose Lissajous plot is irregular in shape), indicating that these samples have a perfect elastic interface response or a viscoelastic response dominated by the elastic component, respectively. The interfacial layer formed by the CS-TiO2-3% sample seems to respond differently to tension and compression. As the strain amplitude increases further, some Lissajous curves become a bit narrow, such as CS-TiO2-0.1% and CS-TiO2-1% (indicating the presence of some viscous dissipation), while some Lissajous curves become slightly sigma-shaped, such as CS-TiO2-0.3% and CS-TiO2-1% (indicating the presence of shear thinning behavior in the viscous response). There are obvious differences in the areas enclosed by the obtained Lissajous curves, which indicates that there are differences in the energy dissipation per unit volume of different CS-TiO2 samples in one cycle, and the energy dissipation of CS-TiO2-1% composite materials in one cycle is larger than that of other composites. During the interface expansion process, the distance between CS-TiO2 molecules at the interface increases, which will weaken or reduce the interaction between CS and TiO2 molecules, thereby causing an elastic response of linear viscoelasticity of the interface layer. Therefore, the interfacial film layer will become more like a fluid material and show strain softening. It has also been reported that polysaccharides have similar interfacial behaviors under different pH conditions and concentrations. In the present invention, when the TiO2 concentration is 0.5%, the shape and slope of the Lissajous plot do not change significantly at any amplitude, indicating that the external strain applied within this range may be relieved by the complete compounding of TiO2 and CS through sufficient and effective intermolecular interactions, thereby forming a complete and strong interface layer and a stable emulsion system that can resist deformation and show a perfect elastic interface response. However, as the TiO2 concentration increases, the Lissajous plot appears elliptical (CS-TiO2-1%) or asymmetric and irregular (CS-TiO2-3%), indicating that the interface film layer has a nonlinear viscoelastic response.
[0130] In order to study the precise changes in the interfacial film, the S factor value was determined. Fig.11As shown in the figure, the absolute S factor values of samples with lower TiO2 concentration (0%-0.5%) during tension or compression are all lower than 0.2 within the amplitude range examined, indicating that the interface mainly responds in a linear elastic manner. For samples with higher TiO2 concentration (1%-3%), the nonlinear response characteristics become obvious. The S factor value of the sample during compression is less than zero (negative value), indicating that strain softening has occurred in the interfacial film layer. When the interface deformation is large, the strain softening reaction is enhanced, especially for samples with higher titanium dioxide concentration (1%-3%).
[0131] 2.3 Characteristics of CS-TiO2 composite particles stabilizing essential oil emulsions
[0132] 2.3.1 Particle size and microstructure characteristics of emulsions
[0133] Fig.12 Figures A and B show the particle size and zeta potential of CS or composite particle stabilized emulsions. As the TiO2 concentration increases from 0.1% to 3%, the particle size and zeta potential of the CS-TiO2 stabilized emulsion show a V-shaped and inverted V-shaped change pattern, respectively. The sample with a TiO2 concentration of 0.5% has the smallest particle size and the highest positive zeta potential. In the absence of TiO2 and with a low concentration (0%-0.3%) of TiO2, the oil droplets will agglomerate, flocculate and coagulate (e.g. Fig.12 This is probably due to the inability to overcome the energy barrier created by the interaction between the composite particles and the oil, which prevents most of the particles from reaching the interface. The D4,3 and D3,2 of the emulsion containing 0.5% TiO2 were significantly reduced, indicating an enhanced emulsification ability ( Fig.12 A). The composite particles containing 0.5% TiO2 have the lowest interfacial tension, which allows the CS-TiO2-0.5% emulsion system to be effectively emulsified during the emulsification process, thereby forming smaller oil droplets. As the TiO2 concentration increases above 0.5%, the d4,3 and d3,2 values increase again (although the d4,3 and d3,2 values no longer reach as high as those of the emulsion containing 0.5% TiO2). These changes are consistent with the zeta potential and interfacial properties results of the CS-TiO2 composite particles (including contact angle values and anti-interference ability). Fig.12 As shown in Figure C, when the TiO2 concentration increases to 3%, the red area around the droplet surface increases, indicating that the adsorption of the composite particles on the oil droplet surface increases, forming a thicker interface layer. Fig.12As shown in Figure B, except that the zeta potential of the CS-TiO2-3% emulsion is slightly higher than that of the CS-TiO2-1% emulsion, and the zeta potential of the CS-TiO2-3% composite is lower than that of the CS-TiO2-1% composite (which may be due to the influence of the stable oil droplets of the composite and the surrounding continuous water phase), the change trend of the emulsion potential is basically consistent with that of the CS-TiO2 composite particles. It may be that hydrogen bonds are formed between the continuous phase and the excess CS-TiO2 near the droplet surface, thus forming a three-dimensional gel network through self-assembly.
[0134] 2.3.2 Rheological behavior of emulsion
[0135] like Fig.13 As shown in Figures A and B, the storage modulus (G′) and loss modulus (G″) of the emulsion generally increase with increasing frequency, but decrease with increasing TiO2 concentration within the measured frequency range, especially G′ and G″ decrease to levels lower than and comparable to those of the CS-emulsion sample, respectively. These results indicate that the emulsion has a consistent gel network, which is mainly a non-covalent cross-linked structure. In fact, the G′ values of the CS-TiO2 composite particle-stabilized emulsions are always higher than the corresponding G″ values, indicating that they have stronger elastic solid properties, which is closely related to the main elastic response of the O / W interface at different frequencies mentioned above.
[0136] Fig.13 Figure C shows that under the same stress, the G' value of the emulsion initially increases with increasing TiO2 concentration until 0.5%, and then decreases with further increase in TiO2 concentration. As the TiO2 concentration increases from 0.1% to 0.5%, the pressure deformation point moves toward higher pressures, but when the TiO2 concentration increases from 0.5% to 1%, the pressure deformation point moves slightly toward lower pressures. The G' values corresponding to the pressure deformation points of the emulsions are CS-TiO2-0.5%>CS-TiO2-0.3%>CS-TiO2-0.1%>CS-TiO2-1%>CS>CS-TiO2-3%( Fig.13C). These results indicate that the emulsions stabilized by the CS-TiO2 system (except the CS-TiO2-3% system) have a stronger three-dimensional network structure and a more flexible interface than the emulsions containing CS, which suggests that the addition of an appropriate amount of TiO2 to CS is beneficial for stabilizing Pickering emulsions. TiO2 particles can induce crosslinking through hydrogen bonding with CS and the complexing effect of CS-TiO2, thereby forming a continuous network around the oil droplets and ultimately forming a strong emulsion gel, thereby enhancing the deformation resistance of the emulsion. Within the stress range of all TiO2 concentrations, the G′ value is always higher than the corresponding G″ (data not shown), which further confirms that the CS-TiO2 composite stabilized emulsion (TiO2 concentration of 0.1-1%) is a gel solid with an elastic and soft network structure, and its integrity is enhanced. Within the range of applied stress, the CS-TiO2-3%-emulsion has the lowest G′ value, indicating that its elastic structure is poor due to the agglomeration of oil droplets.
[0137] Fig.13 D shows the CS-TiO2 composite stable emulsion in 1-100s -1 The shear thinning behavior in the shear rate range is due to the gradual rupture of the latex gel structure under increasing shear conditions. In the static or low flow state, the CS-CS and CS-TiO2 molecules are entangled with each other, resulting in a relatively high viscosity. However, due to the different shear stresses between different flow layers, with increasing flow and shear rate, the relatively dispersed particles or chains roll and rotate, thereby reducing the number of interconnections and causing shear thinning. The Ostwald-deWaele model was used to fit the experimental data of the apparent viscosity of the emulsions as a function of shear rate obtained from rheological analysis, and a high correlation coefficient (R 2>0.98). As shown in Table 2, the n values are all less than 1 (CS, 0.436; CS-TiO2-0.1%-1% <3; CS-TiO2-3%, 0.549), indicating that all the emulsion samples tested are non-Newtonian pseudoplastic fluids, and the shear rate has a significant effect on the apparent viscosity. At the same shear rate, the apparent viscosity values of the tested emulsions are CS-TiO2-0.1%>CS-TiO2-0.3%>CS-TiO2-0.5%CS-TiO2-1%>CS>CS-TiO2-3%. The trend of K value is CS-TiO2-0.5%>CS-TiO2-0.3%>CS-TiO2-0.1%>CS-TiO2-1%>CS>CS-TiO2-3% (Table 2). These findings may be due to the presence of a large number of intermolecular hydrogen bonds and electrostatic interactions between the microparticle groups, which makes the entangled transient network more extensive and dense, thereby increasing the viscosity of the emulsion. The maximum K value (46.321) of the sample containing 0.5% TiO2 indicates that the coordination interaction between TiO2 and CS is quite complete, and a strong electrostatic attraction appears in the emulsion, thereby increasing the entanglement between molecules. For the emulsion stabilized by CS alone, there are only intermolecular hydrogen bonds and weak intermolecular electrostatic interactions between CS molecules, resulting in a lower apparent viscosity. In the present invention, the apparent viscosity of the emulsion stabilized by the composite material containing 3% TiO2 is lower than that of the emulsion stabilized by CS alone.
[0138] Table 2 Ostwald-Dewaele model parameters (K, n and R) of emulsions 2 )
[0139]
[0140] Note: The values are expressed as "mean ± standard deviation". Different letters in the same column (af) indicate significant differences (P<0.05).
[0141] 2.4 Sustained release kinetic model and antibacterial effect of emulsion
[0142] 2.4.1 Sustained-release properties and antibacterial effects of emulsions
[0143] Due to the volatility of EO, EO evaporated from all tested emulsions during the 21-day storage period, and the amount of EO released from each emulsion increased with the extension of storage time ( Fig.14Figure A). After the same storage time, the EO volatilization in the emulsions stabilized by CS and CS-TiO2 was less than that in the sample with EO alone. Compared with the emulsion stabilized by CS alone, the presence of titanium dioxide in the CS matrix reduced the EO volatilization in the emulsion. The presence of emulsion droplets extended the migration distance of EO to the water-air interface and made the intermolecular interaction between EO and the outer layer of the emulsion droplets more complicated, which was closely related to the particle size of the composite particles, the zeta potential interface characteristics, and the droplet size, zeta potential and the rheological properties of the bulk phase of the emulsion. Fig.14 Figure B shows the relative cumulative release curves of oil or emulsion samples at 25°C, which can be divided into three stages according to the change in the slope (release rate) of the release curve. The first stage is shorter (3 days for EO alone; 0.8 days for CS and CS-TiO2 stable emulsions), during which the release rate is the highest. The second stage is from the 3rd to the 7th day for EO and from the 0.8th to the 7th day for CS and CS-TiO2 stable emulsions. During this period, the release rate of all tested samples is decreasing, among which the release rate of CS sample and CS-TiO2-3% emulsion from the 0.8th to the 5th day is much higher than that of other CS-TiO2 stable emulsions. The rapid release of EO in a short period of time at the beginning of storage is conducive to the timely and effective inhibition and / or killing of harmful microorganisms in the early stage of food spoilage. The rapid release of EO in CS-TiO2-3% stable emulsion is closely related to the distinct characteristics of other CS-TiO2 stable emulsions (as mentioned above). In the third stage (7-21 days), the evaporation rate is much lower than that of the first two stages, indicating that the release has reached equilibrium and the emulsion has reached a stable state.
[0144] The antibacterial effects of EO and its derivative emulsions on Escherichia coli and Staphylococcus aureus after storage for 1 or 7 days were evaluated based on the size of the inhibition zone. After the first day of storage, the EO group showed a larger inhibition zone ( Fig.14 C), this is because the EO sample alone released more antibacterial volatiles within the first day. After 7 days of storage, the effect of the EO sample on the inhibition zone remained basically unchanged due to the almost complete volatilization of the antibacterial volatiles, while significant inhibition zones of different diameters were observed for the CS and CS-TiO2 stabilized emulsions. CS-TiO2-0.5% and CS-TiO2-1% emulsions showed the highest antibacterial efficacy against the two tested strains. These results are consistent with the relative cumulative release of the antibacterial agents ( Fig.14 B) and other factors such as the contact angle value of the composite material. For example, the contact angle reflects not only the water resistance but also the contact between the microbial cells and the CS-TiO2 composite film layer. The detected antibacterial effect may also come from the TiO2 particles and CS molecules in the CS-TiO2 composite film layer.
[0145] 2.4.2 Slow release of essential oil volatiles from emulsions
[0146] To analyze the volatile release mechanism of EO in the emulsion, various mathematical models and related analyses were used. Table 3 shows the fitting results of the emulsion release kinetic data with several commonly used models. The fitting quality and accuracy were evaluated according to the coefficient of determination (R 2 ) and the exponential diffusion constant (i.e., the release exponent, n). The Rigter-Peppas model may be the best model representing the release of EO volatiles from the CS-TiO2 stabilized emulsion, and its R 2 value exceeded 0.9. When n ≤ 0.43, the diffusion process was classified as normal / Fickian diffusion; when 0.43 < n < 0.85, the diffusion process was classified as non-Fickian diffusion (anomalous transport); when n ≥ 0.85, the diffusion process was related to degradation during polymer dissolution or swelling. In the present invention, the n values of the tested samples (including samples using EO alone, CS- / CS-TiO2 stabilized emulsions) were all lower than 0.43, indicating that Fickration occurred during the emulsion swelling process. It was shown that Fickian diffusion occurred in all tested samples, that is, due to the relatively high initial EO content, the EO volatiles initially underwent a diffusion and then a release (the diffusion driven by the initial EO concentration decreased and the release rate slowed down) until the emulsion structure was damaged due to continuous release.
[0147] Table 3 Fitting parameters of emulsion release kinetic data with different models
[0148]
[0149] Note: Oil refers to perilla essential oil.
[0150] Fig.15 Figure A shows the results of the correlation analysis of the interfacial adsorption, stability of the emulsion, and the slow release of composite particles and the emulsion. In Fig.15 Figure A, the slow release characteristics were positively correlated with the interfacial pressure, composite particle size, composite particle potential, composite contact angle, emulsion particle size, and emulsion potential, while negatively correlated with the diffusion rate, permeation rate, release kinetics, and release rate. Fig.15Figure B is a schematic diagram of this correlation, and the following slow release mechanism: Initially, the emulsion fixes / surrounds a large amount of EO. However, incomplete / inadequate emulsification causes EO to migrate from areas with higher EO concentration to areas with lower EO concentration (surface diffusion dominates this stage, with osmotic pressure and convection as the main influencing factors). Once the "free" EO has evaporated, the release of EO fixed / enclosed in the emulsion by the composite particles becomes dominant. At this stage, the CS-TiO2 composite particles are formed by physical or chemical interactions between CS and TiO2 in an appropriate ratio. The adsorption capacity of CS-TiO2 composites on oil droplets is closely related to interfacial tension and viscoelasticity. The diffusion rate of composite particles from the continuous phase to the interface is controlled by the concentration gradient. After reaching the O / W interface, the composite particles will entangle, reorganize and self-align with each other through various molecular interactions such as electrostatic interaction, hydrogen bonding and hydrophobic interaction, which promotes the penetration of hydrophobic groups on these molecules into the oil phase, and finally forms a continuous viscoelastic interfacial film layer, which surrounds the oil droplets and hinders the release of EO molecules. If there is some or even excess TiO2 in the aqueous phase of the emulsion system, this "extra" TiO2 may be present in the form of TiOH and TiOH2 + In addition, the presence of a large amount of TiOH may increase the local pH, leading to the deprotonation of TiOH to TiO - , and produce a negatively charged area on the surface of the composite material, which repels surface water molecules in the local environment. These events will promote changes in the interfacial film layer, including the penetration and subsequent rearrangement of the interfacial film layer (although the penetration process is slower than the rearrangement process, as shown in Table 1). All of these events will change the surface charge, wettability, thickness, structure and integrity of the interfacial film layer, so that the CS-TiO2 system can slow down the release of EO antibacterial volatile substances in the composite stable emulsion. In particular, the interfacial properties of the film layer on the droplet and the stability of the emulsion play a crucial role in the release of EO. Many previous studies have suggested that Pickering emulsions are ideal EO sustained-release systems because of their high stability compared to traditional emulsions. Zhao et al. (2024) pointed out that the barrier-induced interception effect of the emulsion interface promotes the sustained release of EO. In the present invention, CS-TiO2 composite particles can form an irreversible interfacial monolayer or multilayer three-dimensional elastic network gel structure on the EO oil droplets. These interfacial layers wrap the EO phase and prevent the collision, agglomeration, flocculation and coagulation of the oil droplets (such as Fig.12 Densely distributed and well-separated oil droplets in the emulsion can extend the migration distance of EO to the water-air interface and introduce more intermolecular interactions between EO molecules and the interfacial layer, thereby maintaining the long-term sustained release of EO.
[0151] 3 Conclusion
[0152] The present invention first modifies TiO2 with sodium laurate under the condition of pH 5.0, and then successfully introduces it into a chitosan (CS) matrix to prepare CS-TiO2 composite particles. The CS-TiO2 composite particles with a TiO2 concentration of 0.1%-1% can be entangled and rearranged with each other through intramolecular and intermolecular interactions, forming a stable, flexible and viscoelastic three-dimensional gel network film at the O / W interface, mainly showing elastic solid-state-like properties and high anti-interference ability. The Perilla essential oil (PLEO) Pickering emulsion stabilized by these composite particles is a non-Newtonian pseudoplastic fluid with shear thinning, slow release and antibacterial properties. CS-TiO2-0.5% and CS-TiO2-1% composite particles show excellent performance when producing such emulsions (i.e., the emulsions have the highest antibacterial efficacy against Escherichia coli and Staphylococcus aureus), among which the CS-TiO2-0.5% composite particles show unique advantages. The results of the sustained release kinetics and mathematical modeling studies showed that Fickian diffusion and sustained sustained release of PLEO occurred in all the studied Pickering emulsions, and the Rigter-Peppas model may be the best model to describe the release of PLEO from CS-TiO2 stabilized emulsions. The sustained release characteristics were positively correlated with the interfacial pressure, composite particle size, composite particle potential, composite contact angle, emulsion particle size and emulsion potential, but negatively correlated with the diffusion rate, permeation rate, release kinetics and release rate. CS-TiO2 stabilized polyLEO emulsions can produce an antibacterial effect while sustaining the sustained release of polyLEO, which will bring dual benefits to food applications (such as antibacterial packaging and bioactive delivery).
[0153] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a Perilla essential oil Pickering emulsion, characterized in that: The following steps are involved: The sodium laurate and titanium dioxide particles are mixed and reacted to obtain modified titanium dioxide particles; adding the modified titanium dioxide particles into a chitosan solution to react and obtain chitosan-titanium dioxide composite particles; dispersing the chitosan-titanium dioxide composite particles in water to obtain a chitosan-titanium dioxide composite particle suspension; Adding perilla essential oil dropwise into the chitosan-titanium dioxide composite particle suspension, and subjecting the suspension to homogenization, to obtain the perilla essential oil Pickering emulsion; The mass ratio of the chitosan to the modified titanium dioxide particles is 1:(0.5-1); The mass ratio of the sodium laurate to the titanium dioxide particles is 0.75:5; The pH value of the mixed reaction is 5.0; The temperature of the mixed reaction is 40° C. and the time is 4 hours.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the chitosan to the modified titanium dioxide particles is 1:0.
5.
3. The preparation method according to claim 1, characterized in that: The volume ratio of the perilla essential oil to the chitosan-titanium dioxide composite particle suspension is 1:
1.
4. A Perilla essential oil Pickering emulsion prepared according to the preparation method according to any one of claims 1 to 3.
5. Use of the Perilla essential oil Pickering emulsion as claimed in claim 4 in the preparation of an antibacterial agent or a preservative.
Citation Information
Patent Citations
Plant growth sterilization accelerator and preparation process for same
CN103772025A
Compound environment-friendly material for freshness retaining and sterilization after harvesting of agricultural products, preparing method and application
CN109984190A
Method for synergistically preparing Pickering emulsion from soybean seed coat polysaccharide and silicon dioxide particles
CN115430306A